Features of bioregulatory therapy in gynecological practice (review) - O I Lineva (Гинекология, 2016)
Bioregulatory approach and by its principles bioregulatory complex preparations such as Traumeel® S have the ability to influence midget doses, activation of detoxification and recovery of self-regulation processes. This review presents the current published data on the effectiveness of medication Traumeel® S in treatment of certain gynecological diseases in accordance with the principles of bioregulatory medicine.